Using 4MOST to refine the measurement of galaxy properties : a case study of supernova hosts - Dumayne, J.; Hook, I.M.; Williams, S.C.; Lowes, G.A.; Head, D.; Fritz, A.; Graur, O.; Holwerda, B.; Humphrey, A.; Milligan, A.; Nicholl, M.; Roukema, B.F.; et al. (Oxford University Press, 2025)
The Rubin Observatory’s 10-yr Legacy Survey of Space and Time will observe near to 20 billion galaxies. For each galaxy the properties can be inferred. Approximately 105 galaxies observed per year will contain Type Ia supernovae (SNe), allowing SN host-galaxy properties to be calculated on a large scale. Measuring the properties of SN host galaxies serves two main purposes. The first is that there are known correlations between host galaxy type and SN type, which can be used to aid in the classification of SNe. Secondly, Type Ia SNe exhibit correlations between host-galaxy properties and the peak luminosities of the SNe, which has implications for their use as standardizable candles in cosmology. We have used simulations to quantify the improvement in host-galaxy stellar mass (M∗) measurements when supplementing photometry from Rubin with spectroscopy from the 4-metre Multi-Object Spectroscopic Telescope (4MOST) instrument. We provide results in the form of expected uncertainties in M∗ for galaxies with 0.1 < z < 0.9 and 18 < rAB < 25. We show that for galaxies mag 22 and brighter, combining Rubin and 4MOST data reduces the uncertainty measurements of galaxy M∗ by more than a factor of 2 compared with Rubin data alone. This applies for elliptical and Sc-type hosts. We demonstrate that the reduced uncertainties in M∗ lead to an improvement of 7 per cent in the precision of the ‘mass step’ correction. We expect our improved measurements of host-galaxy properties to aid in the photometric classification of SNe observed by Rubin.